Comparative responsiveness of the PROMIS-10 Global Health and EQ-5D questionnaires in patients undergoing total knee arthroplasty. (July 2019) - Shim, J.; Hamilton, D. F.
Abstract : Aims: Responsiveness to clinically important change is a key feature of any outcome measure. Throughout Europe, health-related quality of life following total knee arthroplasty (TKA) is routinely measured with EuroQol five-dimension (EQ-5D) questionnaires. The Patient-Reported Outcomes Measurement Information System 10-Question Short-Form (PROMIS-10 Global Health) score is a new general heath outcome tool which is thought to offer greater responsiveness. Our aim was to compare these two tools. Patients and Methods: We accessed data from a prospective multicentre cohort study in the United Kingdom, which evaluated outcomes following TKA. The median age of the 721 patients was 69.0 years (interquartile range, 63.3 to 74.6). There was an even division of sex, and approximately half were educated to secondary school level. The preoperative EQ-5D, PROMIS-10, and Oxford Knee Scores (OKS) were available and at three, six, and 12 months postoperatively. Internal responsiveness was assessed by standardized response mean (SRM) and effect size (Cohen's d ). External responsiveness was assessed by correlating change scores of the EQ-5D and PROMIS-10, with the minimal clinically important difference (MCID) of the OKS. Receiver operating characteristic (ROC) curves were used to assess the ability of change scores to discriminate between improved and non-improved patients. Results: All measures showed significant changes between the preoperative score and the various postoperative times (p < 0.001). Most improvement occurred during the first three months, with small but significant changes between three and six months, and no further change between six and 12 months postoperatively. SRM scores for EQ-5D, PROMIS-10, and OKS were large (> 0.8). ROC curves showed that both EQ-5D and PROMIS-10 were able to discriminate between patients who achieved the OKS MCID and those who did not (area under the curve (AUC) of 0.7 to 0.82). Conclusion: The PROMIS-10 physical health tool showed greater responsiveness to change than the EQ-5D, most probably due to the additional questions on physical health parameters that are more susceptible to modification following TKA. The EQ-5D was, however, shown to be sensitive to clinically meaningful change following TKA, and provides the additional ability to calculate health economic utility scores. It is likely, therefore, that EQ-5D will continue to be the global health metric of choice in the United Kingdom. Cite this article: Bone Joint J 2019;101-B:832–837.